2007
DOI: 10.1111/j.1365-2702.2007.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent severe fatigue in patients with rheumatoid arthritis

Abstract: Fatigue in patients with rheumatoid arthritis has to be considered as a symptom that needs to be addressed by professionals in the same way as pain and disability. In current care, fatigue is insufficiently addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 35 publications
5
95
0
2
Order By: Relevance
“…The univariate analysis revealed that women experienced significantly more fatigue than men, in accordance with previous studies in the area (19,(21)(22)(23) . This finding may be the result of factors like the prevalence of depressive symptoms among women, female physical characteristics and gender-specific workloads.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The univariate analysis revealed that women experienced significantly more fatigue than men, in accordance with previous studies in the area (19,(21)(22)(23) . This finding may be the result of factors like the prevalence of depressive symptoms among women, female physical characteristics and gender-specific workloads.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in a study conducted in Norway, disabled people were more fatigued than subjects at work (21) ; and in a study on rheumathoid arthritis patients, disability was also a predictor of fatigue (23) . Unfortunately, in the present study, it was not possible to determine whether or not the occupational status of sick-listed patients increased their fatigue.…”
Section: Discussionmentioning
confidence: 85%
“…In RA, fatigue is a frequently occurring and patientrelevant symptom that often is experienced as debilitating and restricting daily functioning (2). In cross-sectional studies, it is found that at least 40% of the patients with RA have severe fatigue (3,4). Pain and fatigue are the symptoms mentioned by RA patients as the most disturbing symptoms of the disease (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the subtypes may inform stratified treatment approaches. Fatigue is not only a significant predictor of disability, poor quality of life and reduced well-being but also of medical costs and employment loss (3,(41)(42)(43)(44) and its alleviation is clearly important for patients. Future studies should be conducted to test the predictive value of these sub-types within the context of trials, for example testing the efficacy of cognitive behavioural therapy on 'affective fatigue' or more aggressive immunomodulation for 'inflammatory fatigue' may ultimately lead to a personalised approach to fatigue management.…”
Section: Discussionmentioning
confidence: 99%